Ethnochemical Reconstruction of Dayak Tomun Tuak Fermentation for Contextual Chemistry Learning: an Applied Ethnography with AI-Augmented Qualitative Analysis - Deby Maghfira Prameswari; Woro Sumarni; Harjono Harjono (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
This study integrates AI-augmented qualitative analysis into an applied-ethnographic reconstruction of Dayak Tomun tuak fermentation to address the lack of curriculum-ready, place-based chemistry materials. Fieldwork in Arut Selatan, Central Kalimantan (August 2024–January 2025) engaged two participants (one brewer, one customary leader) through structured observation, semi-structured narrative interviews, and audiovisual documentation under inclusion criteria of ≥10 years’ practice and consistent use of traditional methods. Within Google Colab, ChatGPT assisted transcript segmentation and first-pass open–axial–selective coding; researchers verified all outputs line by line and iteratively refined a codebook with an audit trail. Findings clarify a two-stage process: glutinous-rice tapai for approximately 2–3 days followed by fermentation of a cooled sugar-and-spice infusion for approximately 4–5 days. Three controls consistently mattered: cooling to hand-warm (≤35 °C) before inoculation, tightly sealed vessels for defined durations, and spice infusion (clove, cinnamon, nutmeg, long pepper, black pepper) for flavor and perceived “cleanliness.” Sensory shift from sweet to bitter aligned with community assessments of progress; sociocultural boundaries (acid exclusion, restricted access, optional kapur sirih markings) co-occurred with empirical controls. We provide four curriculum-aligned exemplars for Grades 10–11: stoichiometry and reaction progress with simulated sucrose musts; anaerobiosis and gas balance via sealed-jar CO₂ capture; phenolic antioxidant assays (DPPH) using culinary spices with safety notes; and pH-shift demonstrations framed by the acid-exclusion hypothesis. Limitations include no instrumental ABV, pH, or microbiome data; pathway figures are interpretive. Future work should prioritize spot pH/Brix and hydrometer ABV, along with microbiome–metabolome mapping to strengthen the scientific and educational bridge.